Incidencia de la emergencia sanitaria covid-19 en la gestión administrativa de la ESPAM “MFL” durante el año 2020 - Ormaza Alcívar, Génesis Yulen (2021)
The main objective of the research was to carry out an analysis of the incidence of the covid-19 health emergency in the administrative management of the Escuela Superior Politécnica Agropecuaria de Manabí "MFL", for this, three phases were carried out in the methodological development, the The first consisted of identifying the guidelines established in the essential activities of administrative management, in addition to organizing the information obtained through tools such as the interview with the Rector of the institution, the Director of Human Talent, the Analyst of the area of Security and Occupational Health and the Financial Director, likewise, the survey was carried out to the administrative servants; In the second phase, the information obtained was tabulated in such a way that by means of this the variables with the greatest incidence in administrative management were identified, later, a weighting matrix classified into three relevant factors obtained from the research was made, such as: distance work with an average of (4.07), administrative management with (3.31) and involvement of administrative staff with (3.12) out of a total of 5 as described by the likert scale, which allowed to know specifically what the factors were with greater affectation in the administrative management; In the third phase, with the information collected and weighted, the SWOT matrix was prepared, where it was possible to identify the strengths, opportunities, weaknesses and threats that arose in administrative management due to the pandemic, and in turn, strategies that contribute to the improvement of institution.